Resin composition for foam molding, foam molded body, method for producing foam molded body, foamed electric wire, and method for producing foamed electric wire
Patent Information
- Application Number
- CN202580018046.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-04
- Publication Date
- 2026-10-09
AI Technical Summary
[0033]根据本公开,能够提供能够使气泡充分微细化且外观良好的发泡成型用树脂组合物、发泡成型体、发泡成型体的制造方法、发泡电线和发泡电线的制造方法。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This disclosure relates to resin compositions for foaming, foamed bodies, methods for manufacturing foamed bodies, foamed wires, and methods for manufacturing foamed wires. Background Technology
[0002] Fluoropolymers are widely used in various applications due to their excellent heat resistance and chemical resistance.
[0003] Foaming molding is a known method for achieving lightweighting and improved electrical properties of fluoropolymers. In foaming molding, microbubbles can be formed by adding substances that act as nuclei for foaming (foaming nucleating agents).
[0004] Due to the high molding temperature of fluoropolymers, the foaming nucleating agents that can be used are limited, and boron nitride is usually used (for example, see Patent Documents 1-3).
[0005] Existing technical documents
[0006] Patent documents
[0007] Patent Document 1: Japanese Patent Application Publication No. 10-045931
[0008] Patent Document 2: Japanese Patent Application Publication No. 2022-028640
[0009] Patent Document 3: Japanese Patent Application Publication No. 2005-206745 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] However, there is room for improvement in boron nitride in terms of the inability to fully miniaturize the bubbles.
[0012] Furthermore, Patent Document 1 discloses a method for miniaturizing bubbles by mixing a salt of perfluoroalkyl sulfonic acid or the like with boron nitride. However, if a fluorinated surfactant such as perfluoroalkyl sulfonic acid is mixed in, the molten resin during molding is plasticized, which sometimes generates sparks and damages the appearance. There is room for improvement in this regard.
[0013] The purpose of this disclosure is to provide a resin composition for foaming molding that can sufficiently miniaturize bubbles and produce a good appearance, a foamed molded body, a method for manufacturing a foamed molded body, a foamed wire, and a method for manufacturing a foamed wire.
[0014] Methods for solving problems
[0015] This disclosure (1) is a resin composition for foaming molding, comprising a fluoropolymer (A) and a tetrapyrrole cyclic compound (B).
[0016] This disclosure (2) is a resin composition for foaming as described in this disclosure (1), wherein the fluororesin (A) is a fluororesin capable of melt molding.
[0017] This disclosure (3) is a resin composition for foaming molding as described in disclosure (1) or (2), wherein the fluororesin (A) is at least one selected from the group consisting of tetrafluoroethylene / hexafluoropropylene copolymers and tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.
[0018] This disclosure (4) is a foaming resin composition as described in any one of (1) to (3) of this disclosure, wherein the fluororesin (A) is a tetrafluoroethylene / hexafluoropropylene copolymer.
[0019] This disclosure (5) is a foaming resin composition as described in any one of disclosures (1) to (4), wherein the fluororesin (A) is fluorinated.
[0020] This disclosure (6) is a foaming resin composition as described in any one of disclosures (1) to (5), wherein the content of the fluororesin (A) is 80 to 99.99% by mass.
[0021] This disclosure (7) is a foaming resin composition as described in any one of disclosures (1) to (6), wherein the content of the fluororesin (A) is 97% by mass or more and less than 99.85% by mass.
[0022] The foaming resin composition of this disclosure (8) as described in any one of disclosures (1) to (7) is substantially free of fluorine-based low molecular weight compounds.
[0023] This disclosure (9) is a foaming resin composition as described in any one of disclosures (1) to (8), wherein the tetrapyrrole cyclic compound (B) has a phthalocyanine skeleton.
[0024] This disclosure (10) is a foaming resin composition as described in any one of disclosures (1) to (9), wherein the tetrapyrrole cyclic compound (B) is a metal phthalocyanine.
[0025] This disclosure (11) is a resin composition for foaming molding as described in any one of disclosures (1) to (10), wherein the tetrapyrrole cyclic compound (B) is copper phthalocyanine.
[0026] This disclosure (12) is a foaming molding resin composition as described in any one of disclosures (1) to (11), wherein the content of the tetrapyrrole cyclic compound (B) is 0.1 to 20 parts by weight relative to 100 parts by weight of the fluororesin (A).
[0027] This disclosure (13) is a foaming molding resin composition as described in any one of disclosures (1) to (12), wherein the content of the tetrapyrrole cyclic compound (B) is 0.5 to 2.0 parts by weight relative to 100 parts by weight of the fluororesin (A).
[0028] This disclosure (14) is a foamed molded body formed using any one of the foamed molding resin compositions described in any one of disclosures (1) to (13).
[0029] This disclosure (15) is a method for manufacturing a foamed molded body, which includes a step of foaming and molding the resin composition for foaming and molding as described in any one of the disclosures (1) to (13).
[0030] This disclosure (16) is a foamed wire having a conductor and a foamed insulation layer formed on the conductor using any one of the foaming molding resin compositions of this disclosure (1) to (13).
[0031] This disclosure (17) is a method for manufacturing a foamed wire, which includes the step of forming a foamed insulation layer on a conductor using the foaming molding resin composition described in any one of the disclosures (1) to (13).
[0032] Invention Effects
[0033] According to this disclosure, it is possible to provide a resin composition for foaming molding that can sufficiently refine bubbles and produce a good appearance, a foamed molded body, a method for manufacturing a foamed molded body, a foamed wire, and a method for manufacturing a foamed wire. Detailed Implementation
[0034] The following details this disclosure.
[0035] The disclosed resin composition for foaming molding comprises a fluoropolymer (A) and a tetrapyrrole cyclic compound (B).
[0036] In the foaming molding resin composition disclosed herein, a tetrapyrrole cyclic compound (B) functions as a foaming nucleating agent, enabling the formation of fine bubbles compared to the use of boron nitride. Therefore, it can be applied to applications requiring thin molded bodies, such as fine wires.
[0037] Furthermore, compared to the use of fluorinated surfactants, it can suppress the generation of sparks and reduce appearance defects. As a result, it can be used for long-term molding processes such as wire forming.
[0038] Furthermore, not only is the generation of sparks suppressed, but the surface roughness is also reduced, thus improving the electrical properties.
[0039] Fluoropolymer (A) can be any fluorinated resin, but is preferably a melt-processable fluorine resin. Examples of melt-processable fluorine resins include tetrafluoroethylene (TFE) / hexafluoropropylene (HFP) copolymers [FEP], TFE / perfluoro(alkyl vinyl ether) (PAVE) copolymers [PFA], TFE / ethylene copolymers [ETFE], trifluorochloroethylene (CTFE) / ethylene copolymers [ECTFE], polyvinylidene fluoride [PVdF], polychlorotrifluoroethylene [PCTFE], TFE / vinylidene fluoride (VdF) copolymers [VT], polyvinyl fluoride [PVF], TFE / VdF / CTFE copolymers [VTC], TFE / ethylene / HFP copolymers, and TFE / HFP / VdF copolymers. One or more of these can be used.
[0040] Examples of PAVEs mentioned above include perfluoro(methyl vinyl ether) [PMVE], perfluoro(ethyl vinyl ether) [PEVE], and perfluoro(propyl vinyl ether) [PPVE]. Among these, PPVE is preferred. One or more of these can be used.
[0041] Fluoropolymer (A) may contain polymerization units based on other monomers in an amount that does not impair the essential properties of each fluoropolymer. Other monomers may be appropriately selected from, for example, TFE, HFP, ethylene, propylene, perfluoro(alkyl vinyl ether), perfluoroalkyl ethylene, hydrofluoroolefin, fluoroalkyl ethylene, perfluoro(alkyl allyl ether), etc. One or more of these may be used. As the perfluoroalkyl group constituting the other monomer, a perfluoroalkyl group having 1 to 10 carbon atoms is preferred.
[0042] Other monomers can be monomers with polar groups. Examples of monomers with polar groups include hydroxyl alkyl vinyl ethers such as hydroxyethyl vinyl ether, hydroxypropyl vinyl ether, hydroxybutyl vinyl ether, hydroxyisobutyl vinyl ether, and hydroxycyclohexyl vinyl ether (all non-fluorinated monomers with hydroxyl groups); acrylic acid, methacrylic acid, itaconic acid, succinic acid, fumaric acid, crotonic acid, maleic acid, citraconic acid, undecenoic acid, and ethynyl dicarboxylic acid (all non-fluorinated monomers with carboxyl groups); itaconic anhydride (hereinafter also denoted as "IAH"), citraconic anhydride (hereinafter also denoted as "CAH"), and 5-norbornene. Non-fluorinated monomers with anhydride residues, such as 2,3-dicarboxylic anhydride (hereinafter also referred to as "NAH"), succinic anhydride, fumaric anhydride, and maleic anhydride; non-fluorinated monomers with sulfonic groups, such as vinyl sulfonic acid; non-fluorinated monomers with epoxy groups (glycidyl groups), such as glycidyl vinyl ether and glycidyl allyl ether; non-fluorinated monomers with amino groups, such as aminoalkyl vinyl ether and aminoalkyl allyl ether; non-fluorinated monomers with amide groups, such as (meth)acrylamide and hydroxymethylacrylamide; and non-fluorinated monomers with nitrile groups, such as acrylonitrile and methacrylonitrile.
[0043] From the perspective of excellent heat resistance, the fluoropolymer (A) is preferably at least one selected from the group consisting of TFE / HFP copolymers and TFE / PAVE copolymers, and more preferably a TFE / HFP copolymer. Furthermore, from the perspective of superior electrical properties, a perfluorinated resin is also preferred.
[0044] The TFE / HFP ratio of the TFE / HFP copolymer is preferably 80-97 / 3-20 by mass, and more preferably 84-92 / 8-16.
[0045] TFE / HFP copolymers can be binary copolymers composed of TFE and HFP, or terpolymers composed of TFE, HFP and comonomers that can copolymerize with TFE and HFP (e.g., TFE / HFP / PAVE copolymers).
[0046] TFE / HFP copolymers are also preferably TFE / HFP / PAVE copolymers containing PAVE-based polymerization units.
[0047] The TFE / HFP / PAVE copolymer preferably has a mass ratio of 70–97 / 3–20 / 0.1–10, more preferably 81–92 / 5–16 / 0.3–5.
[0048] The TFE / PAVE ratio of the TFE / PAVE copolymer is preferably 90-99 / 1-10 by mass, and more preferably 92-97 / 3-8.
[0049] The TFE / ethylene molar ratio of the TFE / ethylene copolymer is preferably 20–80 / 20–80, more preferably 40–65 / 35–60. Furthermore, the TFE / ethylene copolymer may contain other monomer components.
[0050] That is, TFE / ethylene copolymers can be binary copolymers composed of TFE and ethylene, or terpolymers composed of TFE, ethylene and comonomers that can copolymerize with TFE and ethylene (e.g., TFE / ethylene / HFP copolymers).
[0051] TFE / ethylene copolymers are also preferably TFE / ethylene / HFP copolymers containing HFP-based polymerization units. The molar ratio of TFE / ethylene / HFP in the TFE / ethylene / HFP copolymer is preferably 40-65 / 30-60 / 0.5-20, more preferably 40-65 / 30-60 / 0.5-10.
[0052] In this specification, the melt flow rate (MFR) for melt molding is preferably 1 to 100 g / 10 min. The MFR of the fluoropolymer (A) is more preferably 5 to 70 g / 10 min, further preferably 10 to 60 g / 10 min, and even more preferably 15 to 50 g / 10 min, even more preferably 20 to 45 g / 10 min, and particularly preferably 30 to 45 g / 10 min, from the perspective of suppressing spark generation and increasing foaming rate.
[0053] The above MFR is a value measured according to ASTM D-1238, using a die with a diameter of 2.1 mm and a length of 8 mm, at 372°C and a load of 5 kg.
[0054] Fluororubber (A) may contain non-meltable fluoropolymers along with meltable fluoropolymers. When fluoropolymer (A) contains non-meltable fluoropolymers, their content relative to the total amount of fluoropolymer (A) is preferably 0.001 to 3.0% by mass.
[0055] It should be noted that, in this specification, "unable to melt-form" means that the above-mentioned MFR is less than 1 g / 10 minutes. The above-mentioned MFR is preferably less than 0.1 g / 10 minutes.
[0056] Examples of non-melt-formable fluoropolymers include polytetrafluoroethylene (PTFE). Other examples of melt-formable fluoropolymers include FEP, PFA, ETFE, PCTFE, and PVDF. One or more of these can be used. PTFE is preferred.
[0057] It should be noted that FEP and other fluoropolymers are non-melt-forming when the MFR is less than 1 g / 10 min, and are melt-forming when the MFR is greater than 1 g / 10 min.
[0058] In this disclosure, PTFE can be a tetrafluoroethylene [TFE] homopolymer or a modified polytetrafluoroethylene [modified PTFE] obtained from TFE and trace amounts of comonomers.
[0059] TFE homopolymers are obtained by polymerizing only tetrafluoroethylene [TFE] as a monomer. As trace comonomers in modified PTFE, there are no particular limitations on any fluorinated compound that can copolymerize with TFE; examples include perfluoroolefins such as hexafluoropropylene [HFP]; various perfluorovinyl ethers [PFVE] such as PAVE; fluorinated m-dioxane; trifluoroethylene; and vinylidene fluoride.
[0060] In modified PTFE, the content of trace monomer units from the above-mentioned trace monomers in all monomer units is typically in the range of 0.001 to 1.0% by mass.
[0061] In this specification, "the content (mass%) of trace monomer units in all monomer units" refers to the mass fraction (mass%) of the trace monomers from which the aforementioned trace monomer units originate in the total amount of monomers from which "all monomer units" originate, i.e., the total amount of monomers constituting the fluoropolymer.
[0062] From the perspective of heat resistance and electrical properties, the standard specific gravity [SSG] of PTFE is preferably 2.15 to 2.30, more preferably 2.25 or less, and even more preferably 2.22 or less.
[0063] High molecular weight PTFE with an SSG of less than 2.15 does not exclude the effects of this disclosure, but it is difficult and impractical to manufacture.
[0064] SSG is a value determined according to ASTM D4895-89, based on the water displacement method.
[0065] When PTFE has a low SSG (Self-Strain Gain), a small amount can increase its biaxial tensile viscosity. When the SSG is high, increasing the amount added will produce the same effect.
[0066] PTFE can be prepared by known methods such as emulsion polymerization and suspension polymerization. Emulsion polymerization is preferred as the polymerization method.
[0067] When PTFE aggregates are present in the foaming resin composition disclosed herein, frequent sparking may occur during wire coating molding, leading to a deterioration in the defect rate. Therefore, the average primary particle size of PTFE is preferably 50 to 800 nm, more preferably 50 to 500 nm.
[0068] The average primary particle size of PTFE is determined as follows: For a polymer latex diluted with water to a solid content of 0.22% by mass, the transmittance of transmitted light at a wavelength of 500 nm per unit length is measured. The average primary particle size of PTFE is obtained by pre-measuring the directional diameter in a transmission electron microscope image. The average primary particle size of PTFE is determined based on a standard curve of the average primary particle size of PTFE and the aforementioned transmittance.
[0069] Fluoropolymer (A) can be synthesized by polymerizing monomer components using common polymerization methods, such as emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, and gas-phase polymerization. Chain transfer agents such as methanol are sometimes used in these polymerization reactions. Fluoropolymer (A) can also be manufactured through polymerization and separation without the use of reagents containing metal ions.
[0070] Fluoropolymer (A) is not particularly limited and may have terminal groups such as -CF3 or -CF2H at at least one site of the polymer backbone and polymer side chain, preferably having a -CF3 terminal group. Fluoropolymers having these terminal groups are obtained by fluorination treatment.
[0071] Unfluorinated fluororesins sometimes possess end groups with unstable thermal and electrical properties, such as -COOH, -CH2OH, -COF, and -CONH2 (hereinafter, such end groups will also be referred to as "unstable end groups"). These unstable end groups can be reduced through the aforementioned fluorination treatment. Fluorinated resin (A) preferably contains few or no of the aforementioned unstable end groups, and more preferably, the total number of the above four unstable end groups and the -CF2H end group is less than 1×10⁻⁶. 6 The number of carbon atoms is 50 or less. If it exceeds 50, poor molding may occur. More preferably, the number of unstable terminal groups is 20 or less, and even more preferably 10 or less.
[0072] In this specification, the number of unstable terminal groups mentioned above is a value obtained from infrared absorption spectroscopy. The aforementioned unstable terminal groups and -CF2H terminal groups may be absent, and all may be -CF3 terminal groups.
[0073] Fluorination can be performed by contacting an unfluorinated fluoropolymer with a fluorinated compound.
[0074] There are no particular limitations on fluorine-containing compounds; any fluorine radical source that generates fluorine radicals under fluorination conditions can be cited. Examples of fluorine radical sources include F2 gas, CoF3, AgF2, UF6, OF2, N2F2, CF3OF, and fluorinated halogens (e.g., IF5, ClF3). One or more of these can be used.
[0075] Fluorine radical sources such as F2 gas can be 100% concentrated, preferably diluted to 5-50% by mass, more preferably to 15-30% by mass, after mixing with an inert gas. Examples of inert gases include nitrogen, helium, and argon; from an economic perspective, nitrogen is preferred.
[0076] The conditions for fluorination are not particularly limited. Molten fluoropolymer can be brought into contact with a fluorinated compound. Fluorination is typically carried out at a temperature below the melting point of the fluoropolymer, preferably 20–220°C, and more preferably 100–200°C. Fluorination usually lasts for 1–30 hours, preferably 5–20 hours.
[0077] Fluorination treatment preferably involves contacting the unfluorinated fluoropolymer with fluorine gas (F2 gas).
[0078] As for the fluoropolymer (A), there are no particular limitations. From the perspective of obtaining a foamed molded article with excellent heat resistance and a wide continuous operating temperature range, a melting point of 200°C or higher, a molding temperature of 250°C or higher, and a thermal decomposition temperature of 300°C or higher are preferred. Furthermore, a melting point of 250°C or higher is more preferred, and 320°C or lower is more preferably preferred. A molding temperature of 300°C or higher is more preferably preferred, and 450°C or lower is more preferably preferred. A thermal decomposition temperature of 350°C or higher is more preferably preferred, and 400°C or higher is even more preferably preferred. The upper limit for the melting point, molding temperature, and thermal decomposition temperature is 600°C or lower.
[0079] In this specification, the melting point is the temperature determined by differential scanning calorimetry (DSC), the molding temperature is the generally recommended temperature suitable for molding, and the temperature at which the resin exhibits fluidity without causing coloration or other resin degradation. The thermal decomposition temperature is the 1% weight loss temperature when heated in air at 10°C / min using TG (thermal weight change measurement). However, the weight loss due to the volatilization of water or water of crystallization observed between 100°C and 200°C is not included. Fluidity is defined as an MFR of 0.0001 or higher at this temperature.
[0080] To reduce signal loss in communication cables, the dielectric constant of the fluororesin (A) is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.3 or less, and most preferably 2.1 or less. A lower limit of 1.0 or more is preferred. Similarly, the dielectric loss tangent is preferably 0.01 or less, more preferably 0.002 or less, even more preferably 0.001 or less, and most preferably 0.0005 or less. A lower limit of 0.0001 or more is preferred. The dielectric constant and dielectric loss tangent of the fluororesin (A) are determined using a cavity resonator method at a frequency of 6 GHz.
[0081] The content of fluoropolymer (A) is preferably 80% by mass or more, more preferably 90% by mass or more. Further preferably 95% by mass or more, particularly preferably 97% by mass or more. As an upper limit, it is preferably 99.99% by mass or less, more preferably 99.85% by mass or less, and even more preferably less than 99.85% by mass.
[0082] The foaming resin composition disclosed herein may contain a resin different from the fluoropolymer (A). Examples of resins different from the fluoropolymer (A) include general-purpose resins such as polyethylene resin, polypropylene resin, vinyl chloride resin, and polystyrene resin; and engineering plastics such as nylon, polycarbonate, polyetheretherketone resin, polyphenylene sulfide resin, polyaryletherketone (PAEK), polyetherketoneketone (PEKK), polyetherketone (PEK), polyetheretherketoneketone (PEEKK), polyethersulfone (PES), liquid crystal polymer (LCP), polysulfone (PSF), amorphous polyarylene ester (PAR), polyether nitrile (PEN), thermoplastic polyimide (TPI), polyimide (PI), polyetherimide (PEI), and polyamide-imide (PAI). One or more of these resins may be used.
[0083] The content of the resin different from fluoropolymer (A) is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 1% by mass or less. The lower limit is not particularly limited and can be 0% by mass.
[0084] The resin composition for foaming molding disclosed herein contains a tetrapyrrole cyclic compound (B) as a foaming nucleating agent.
[0085] Tetrapyrrole cyclic compounds (B) are classified into three types based on their skeletons: phthalocyanine, dihydroporphyrin, and chlorophyll. Additionally, they can form complexes with metals, such as copper, iron, and magnesium.
[0086] From the perspective of its good function as a foaming nucleating agent, as a tetrapyrrole cyclic compound (B), a compound having a phthalocyanine skeleton is preferred, a metal phthalocyanine is more preferred, and a copper phthalocyanine is even more preferred.
[0087] The tetrapyrrole cyclic compound (B) preferably does not decompose, dissolve in the fluororesin (A), or melt at the molding temperature during foaming. That is, when the foaming resin composition of this disclosure is foamed, the tetrapyrrole cyclic compound (B) is preferably a solid in the composition. This allows it to fully function as a foaming nucleating agent.
[0088] The condition for a tetrapyrrole cyclic compound (B) to be satisfied can be confirmed by observing whether the compound (B) exists in a solid state when heated to a specified temperature using a polarizing microscope equipped with a hot stage.
[0089] The crystallite size of the tetrapyrrole cyclic compound (B) in X-ray diffraction (XRD) is preferably greater than 100 Å, more preferably greater than 140 Å, and even more preferably greater than 200 Å. This allows for the formation of an ideal lattice with low strain, promoting bubble formation. The upper limit of the crystallite size is preferably 10,000 Å or less, more preferably 5,000 Å or less, and even more preferably 1,000 Å or less.
[0090] XRD was performed using an X-ray diffraction apparatus: Smart Lab, manufactured by Rigaku Corporation, and the powder was measured using SmartLab StudioII software. The X-ray source was CuKα with a wavelength of 1.54 Å, and the diffraction angle (2θ) was set to 5°–90°. The crystallite size was calculated using the Scherrer formula based on the maximum half-width of the obtained diffraction peaks.
[0091] D=K×λ / (β×cosθ)…Scherrer’s formula
[0092] D: Crystalline size (Å)
[0093] K: Scherrer constant
[0094] λ: X-ray wavelength (Å)
[0095] β: Half-width of the diffraction peak (rad)
[0096] θ: 1 / 2 (rad) of the diffraction angle
[0097] Scherrer constant (K) = 0.94, X-ray wavelength (λ) = 1.5418. The case where the obtained diffraction spectrum does not contain diffraction peaks originating from a crystal structure is considered as the case where there is no crystal structure.
[0098] The volatile content of the tetrapyrrole cyclic compound (B) at 330°C is preferably 7.0% by mass or less, more preferably 5.0% by mass or less, even more preferably 3.0% by mass or less, and particularly preferably 1.0% by mass or less. This suppresses the formation of residues (accumulations) that can cause molding defects, enabling long-term molding processes such as wire molding. The lower limit is not particularly limited and can be 0% by mass.
[0099] Regarding the amount of volatilization, the reduction in mass of the sample when it is kept at 330°C for 1 hour in an electric furnace is measured and calculated as the reduction in mass / the mass before holding the sample × 100.
[0100] From the perspective of forming more uniform bubbles, the tetrapyrrole cyclic compound (B) is preferably dispersed in the fluororesin (A) with a center-to-center distance of 5.0 μm or less. The upper limit of the center-to-center distance is more preferably 3.0 μm or less, further preferably 2.0 μm or less, and the lower limit is preferably 0.01 μm or more, more preferably 0.1 μm or more, and further preferably 0.5 μm or more.
[0101] From the perspective of forming more uniform bubbles, the tetrapyrrole cyclic compound (B) is preferably selected with a density of 15,000 bubbles / mm². 2 The above are dispersed in fluororesin (A). A more preferred lower limit for density is 30,000 particles / mm².2 The above is further optimized to 120,000 pieces / mm. 2 The upper limit is preferably 10,000,000 pieces / mm. 2 The following is preferred: 5,000,000 pieces / mm 2 The following is a further preferred value: 1,000,000 pieces / mm 2 the following.
[0102] From the perspective of forming more uniform bubbles, the tetrapyrrole cyclic compound (B) is preferably dispersed in the fluororesin (A) with a particle size of 4.0 μm or less. The upper limit of the particle size is more preferably 3.0 μm or less, further preferably 2.0 μm or less, and the lower limit is preferably 0.001 μm or more, more preferably 0.01 μm or more, and further preferably 0.1 μm or more.
[0103] The dispersion state (intercenter-to-center distance, density, and particle size) of the tetrapyrrole cyclic compound (B) in the fluoropolymer (A) was calculated by image processing of a cross-section of the resin composition containing fluoropolymer (A) and tetrapyrrole cyclic compound (B) taken at 150x magnification using a laser microscope (KEYENCE VK-X1000 shape analysis laser microscope). The intercenter-to-center distance and particle size are average values of 100 particles.
[0104] The melting temperature (melting point) of the tetrapyrrole cyclic compound (B) is preferably 300°C or higher, more preferably 320°C or higher, and even more preferably 350°C or higher. Within this range, it does not easily melt even at the molding temperature during foaming, thus fully realizing its function as a foaming nucleating agent. There is no particular upper limit, but it is preferably 1000°C or lower.
[0105] The thermal decomposition temperature of the tetrapyrrole cyclic compound (B) is preferably 270°C or higher, more preferably 320°C or higher, and even more preferably 350°C or higher. Within this range, it is less prone to decomposition even at the molding temperature during foaming. Therefore, adverse effects caused by the decomposition of the tetrapyrrole cyclic compound (B) (e.g., reduced electrical properties, bubble rupture, and coating breakage during wire molding) can be suppressed. The upper limit is not particularly limited, but is preferably 1000°C or lower.
[0106] The melting temperature (melting point) and thermal decomposition temperature of the tetrapyrrole cyclic compound (B) can be determined using the same method as the fluoropolymer (A) described above.
[0107] In the foaming molding resin composition disclosed herein, the content of tetrapyrrole cyclic compound (B) relative to 100 parts by weight of fluororesin (A) is preferably 0.1 parts by weight or more, more preferably 0.3 parts by weight or more, even more preferably 0.5 parts by weight or more, and preferably 20 parts by weight or less, more preferably 5.0 parts by weight or less, and even more preferably 2.0 parts by weight or less. If the content of tetrapyrrole cyclic compound (B) is too low, the added effect of tetrapyrrole cyclic compound (B) may not be sufficiently obtained; if it is too high, the manufacturing cost may increase.
[0108] The resin composition for foaming molding disclosed herein may contain a foaming nucleating agent other than a tetrapyrrole cyclic compound (B). Examples of foaming nucleating agents other than tetrapyrrole cyclic compounds (B) include boron nitride, sodium 2,2'-methylene bis(4,6-di-tert-butylphenyl) phosphate, barium fluorooctane sulfonate, barium bisphenol phosphate diester, N,N'-dicyclohexyl-2,6-naphthalenedicarboxylate, sodium phenylphosphonate, 2,6-naphthalenedicarboxylic acid, 1,3:2,4-bis-O-(4-methylbenzyl)-D-sorbitol, N,N'-bis(octadecyl)isophthalamide, sodium benzoate, sodium bis(4-nitrophenyl) phosphate, triaminobenzene derivatives, 1,3,5-tris(2,2-dimethylpropionylamino)benzene, Pigment Red 254, talc, sodium binaphthalene phosphate, barium tert-butyl-binaphthalene phosphate, rosin metal salts, and condensed phosphate esters. In addition, sulfonic acid, sulfonates, phosphonic acid, phosphonates, zeolites, ADCA (azodicarbonamide), DPT (N,N'-dinitropentamethylenetetramine), OBSH (4,4'-oxobis(benzenesulfonylhydrazine)), etc. can be used. One or more of them can be used.
[0109] The resin composition for foaming molding disclosed herein may further contain inorganic salts containing polyatomic anions without impairing the effects of the present disclosure.
[0110] Examples of inorganic salts containing polyatomic anions include the substances disclosed in U.S. Patent No. 4,764,538.
[0111] The resin compositions for foaming molding disclosed herein may include conventionally known filler materials to a extent that does not impair the effects of the present disclosure.
[0112] Examples of filler materials include graphite, carbon fiber, coke, silica, zinc oxide, magnesium oxide, magnesium sulfate, tin oxide, antimony oxide, calcium carbonate, magnesium carbonate, magnesium hydroxide, glass, talc, mica, aluminum nitride, calcium phosphate, sericite, diatomaceous earth, silicon nitride, fine silica, fumed silica, alumina, zirconium oxide, quartz powder, kaolin, bentonite, and titanium dioxide. One or more of these materials can be used. The shape of the filler material is not particularly limited and can include fibrous, needle-like, columnar, whisker-like, plate-like, layered, scaly, hollow spherical, porous, short fiber-like, powder-like, granular, and bead-like forms. It should be noted that this filler material differs from boron nitride and other similar materials mentioned in foaming nucleating agents.
[0113] The resin composition for foaming molding disclosed herein may further contain other components such as additives. Examples of other components include fillers such as glass fibers, glass powder, asbestos fibers, cellulose fibers, and carbon fibers, as well as reinforcing agents, stabilizers, lubricants, pigments, flame retardants, and other additives.
[0114] If the resin contains a large amount of fluorine-based low-molecular-weight compounds, the molten resin during molding will be plasticized, sometimes resulting in more sparks. Therefore, the resin composition for foam molding disclosed herein is preferably substantially free of fluorine-based low-molecular-weight compounds.
[0115] It should be noted that, in essence, "free of fluorine-based low molecular weight compounds" means that the content of fluorine-based low molecular weight compounds is less than 10 ppm by mass.
[0116] There are no particular limitations on what constitutes a low-molecular-weight fluorine compound; for example, fluorine compounds with a molecular weight of less than 1000 can be cited. Specifically, perfluoroalkyl acids and perfluorosulfonic acids can be cited, and more specifically, C8F... 17 COOH and its salts, C7F 15 COOH and its salts, C6F 13 COOH and its salts, C8F 17 SO3H and its salts, C6F 13 SO3H and its salts, C4F9SO3H and its salts, C8F 17 CH2CH2-SO3H and its salts, C6F 13 CH2CH2-SO3H and its salts, C8F 17 CH2CH2OH, C6F 13 CH2CH2OH, etc., and more specifically, {F(CF2)6CH2CH2SO3}2Ba can be cited as an example.
[0117] The content of low molecular weight fluorine compounds can be analyzed using the following methods: The sample was pulverized by cryogenic grinding, and the resulting powder was dispersed in methanol. Extraction was then performed by ultrasonic treatment at 60°C for 2 hours. The extract was quantified using liquid chromatography-mass spectrometry (LC-MS / MS), and the obtained value was taken as the content.
[0118] The melt flow rate (MFR) of the resin composition for foaming molding disclosed herein is preferably 1 to 100 g / 10 min. More preferably, it is 5 to 70 g / 10 min, even more preferably 10 to 60 g / 10 min, and from the viewpoint of suppressing spark generation and increasing foaming rate, it is even more preferably 15 to 50 g / 10 min, even more preferably 20 to 45 g / 10 min, and particularly preferably 30 to 45 g / 10 min.
[0119] The above MFR is a value determined according to ASTM D-1238, using a die with a diameter of 2.1 mm and a length of 8 mm, under a load of 5 kg and a temperature of 372 °C.
[0120] To reduce signal loss in communication cables, the dielectric constant of the resin composition for foaming molding disclosed herein is preferably 3.0 or less, more preferably 2.5 or less, even more preferably 2.3 or less, and most preferably 2.1 or less. A lower limit of 1.0 or more is preferred. Similarly, the dielectric loss tangent is preferably 0.01 or less, more preferably 0.002 or less, even more preferably 0.001 or less, and most preferably 0.0005 or less. A lower limit of 0.0001 or more is preferred.
[0121] The dielectric constant and dielectric loss tangent of the resin composition for foaming molding disclosed herein were determined using the resin composition prior to foaming molding via a cavity resonator method at a frequency of 6 GHz.
[0122] The resin composition for foaming molding disclosed herein is suitable for use as a foaming composition, and in particular, is suitable for use as a wire coating composition for forming a coating layer for wires.
[0123] The method for manufacturing a foamed molded article disclosed herein includes a step of foaming a resin composition for foaming molding disclosed herein.
[0124] In addition, the foamed molded articles of this disclosure are formed using the foamed molding resin composition of this disclosure.
[0125] There are no particular limitations on the method for foaming the disclosed resin composition for foaming molding. Conventionally known methods can be used, such as feeding the disclosed resin composition for foaming molding into a screw extruder designed for foaming operation and using a continuous gas extrusion method.
[0126] The gas used in the gas extrusion method can be, for example, dichlorofluoromethane, nitrogen, carbon dioxide, or a mixture of the above gases. It can be introduced as a pressurized gas into the molten resin inside the extruder, or it can be generated by mixing a chemical foaming agent into the molten resin. The introduced gas dissolves in the molten resin inside the extruder.
[0127] Gases dissolved in the resin are expelled from the molten material as the pressure decreases abruptly upon exiting the extrusion die. The extruded material is then cooled and solidified by methods such as introducing it into water.
[0128] The foamed molded body disclosed herein has a low dielectric constant, exhibits stable capacitance, and is lightweight, thus it can be used as a coating material described later to obtain a shape with stable wire diameter, thickness, and other dimensions.
[0129] The total volume of air bubbles in the foamed molded article disclosed herein can be appropriately adjusted, for example, according to the application, by adjusting the amount of gas inserted in the extruder or by selecting the type of dissolved gas.
[0130] The foamed molded body disclosed herein is obtained as a molded body shaped according to its intended use when extruded from the aforementioned extruder. As for the molding method described above, there are no particular limitations as long as it involves heating and melting to form the body; examples include extrusion foaming, injection foaming, and die foaming.
[0131] The shape of the foamed molded body disclosed herein is not particularly limited, and it can be made into various shapes such as coating materials for foamed wires; filaments such as wires; sheets; films; rods; tubes, etc. The aforementioned foamed molded body can be used, for example, as lightweight structural materials such as electrical insulation materials; heat insulation materials; sound insulation materials; suspending materials; and cushioning materials such as cushioning pads. Furthermore, the aforementioned foamed molded body is particularly suitable for use as a coating material for foamed wires.
[0132] The resulting foamed molded article is preferably a foamed molded article containing a melt-cured body of the foamed molding resin composition disclosed herein and bubbles, wherein the bubbles are uniformly distributed in the melt-cured body. The bubble size is not limited, but is preferably 60 μm or less, more preferably 30 μm or less. Furthermore, the bubble size is preferably 0.1 μm or more.
[0133] The foaming rate of the above-mentioned foamed molded article is not particularly limited, but is preferably 20% or more. The upper limit of the foaming rate is not particularly limited, for example, it is 80%.
[0134] The air bubbles in the foamed molded article disclosed herein can be continuous air bubbles or independent air bubbles, preferably independent air bubbles. By using independent air bubbles, the following advantages are available: strong resistance to external pressure, excellent rigidity, impact absorption, and processability; furthermore, moisture and other substances will not penetrate the interior.
[0135] In addition to the heating and melting process mentioned above, independent bubbles can also be formed using previously known methods.
[0136] The foamed molded body disclosed herein is in a foamed state that is conducive to a low dielectric constant, and therefore can be used as an associated insulator for, for example, wire insulation layers, semiconductor packaging substrate insulation layers, transformer insulation layers, circuit board insulation layers, motor insulation layers, reactor insulation layers, transistor insulation layers, printed circuit board insulation layers, semiconductor device insulation layers, electronic component insulation layers, etc., and is particularly suitable for use as wire insulation layers (coating layers).
[0137] The method for manufacturing foamed wires disclosed herein includes a step of forming a foamed insulation layer (coating) on a conductor using the foaming molding resin composition disclosed herein.
[0138] In addition, the foamed wire of this disclosure has a conductor and a foamed insulation layer (coating) formed on the conductor using the foaming molding resin composition of this disclosure.
[0139] The method for forming a foamed insulating layer (coating) on a conductor using the foaming molding resin composition of this disclosure is not particularly limited. Examples include using a gas soluble in molten fluoropolymer (molten resin), feeding the foaming molding composition of this disclosure into a screw extruder designed for foaming operation, and using a continuous gas injection method. The same gas used in the method for manufacturing the foamed molded body can be used as the gas described above.
[0140] The foamed wire disclosed herein has a foamed insulation layer in a foamed state that is conducive to a low dielectric constant, and therefore can suppress signal attenuation compared to conventional wires.
[0141] Materials used as conductors (core wires) can include metallic conductors such as copper and aluminum, as well as carbon. Alternatively, a single material can be used, or the surface can be plated with materials such as silver or tin.
[0142] The conductor diameter is preferably 0.02 to 3 mm. More preferably, the conductor diameter is 0.04 mm or more, even more preferably 0.05 mm or more, and particularly preferably 0.1 mm or more. More preferably, the conductor diameter is 2 mm or less. Furthermore, the conductor can be a single wire or a stranded wire formed by twisting two or more conductors together.
[0143] There are no particular limitations on the shape of a conductor; examples include flat shapes and flat lines.
[0144] Specific examples of conductors (core wires) include AWG (American Wire Gauge)-46 (solid copper wire with a diameter of 40 micrometers), AWG-42 (solid copper wire with a diameter of 64 micrometers), AWG-36 (a wire with a total diameter of 153 micrometers consisting of 7 strands of solid copper wire with a diameter of 127 micrometers and 7 strands of copper wire with a diameter of 51 micrometers), AWG-30 (a wire with a total diameter of 306 micrometers consisting of 7 strands of solid copper wire with a diameter of 254 micrometers and 7 strands of copper wire with a diameter of 102 micrometers), AWG-27 (solid copper wire with a diameter of 361 micrometers), AWG-26 (solid copper wire with a diameter of 404 micrometers), AWG-24 (solid copper wire with a diameter of 510 micrometers), and AWG-22 (solid copper wire with a diameter of 635 micrometers).
[0145] The thickness of the foamed insulation layer (coating layer) is preferably 0.01 to 3.0 mm, and more preferably less than 2.0 mm.
[0146] The surface roughness of the foamed insulation layer (coating layer) is preferably 9.0 μm or less, more preferably 8.0 μm or less, and even more preferably 7.0 μm or less. The lower limit is not particularly limited, but is generally 1.0 μm or more.
[0147] The surface roughness was obtained as follows: The surface of the foamed wire was measured using a laser microscope (VK-X1000) manufactured by KEYENCE. The obtained image data was then subjected to quadratic surface correction for the specified wire area and the correction was performed. The surface roughness within 500×2000μm was then calculated.
[0148] The preferred spark count for the foamed insulation layer (coating) is 200 / 10. 4 For m or less, 80 pieces / 10 is more preferred. 4 For m or less, 30 pieces / 10 is further preferred. 4 Below m. The lower limit is not specifically defined and can be 0 / 10. 4 m.
[0149] The spark count was obtained by measuring the spark count using a Beta LaserMike Sparktester HFS1220 at 1500V.
[0150] The foamed wire disclosed herein can be used as cables for connecting computers and their peripherals, high-speed communication high-capacity image or sound cables, cables connecting servers in data centers, such as LAN cables, USB cables, Lightning cables, Thunderbolt cables, CATV cables, HDMI (registered trademark) cables, QSFP cables, aerospace cables, underground power transmission cables, submarine power cables, high-voltage cables, superconducting cables, packaged wires, automotive cables, wire harnesses / electrical equipment, robot / FA cables, OA equipment cables, information equipment cables (fiber optic cables, audio cables, etc.), internal wiring for communication base stations, high-current internal wiring (inverters, power regulators, battery systems, etc.), internal wiring for electronic equipment, wiring for small electronic equipment / mobile devices, wiring for movable parts, internal wiring for electrical equipment, internal wiring for measuring equipment, power cables (for construction, wind / solar power generation, etc.), control / measurement wiring cables, motor cables, etc.
[0151] The foamed wire disclosed herein can be a two-layer structure (surface-foam) with a non-foam layer inserted between the core wire and the covering material, a two-layer structure (foam-surface) with a non-foam layer covering the outer layer, and a three-layer structure (surface-foam-surface) with a non-foam layer covering the outer layer of the surface-foam.
[0152] As a non-foamed layer, there are no particular limitations; it can be a resin layer composed of TFE / HFP copolymers, TFE / PAVE copolymers, TFE / ethylene copolymers, vinylidene fluoride polymers, polyethylene [PE] and other polyolefin resins, polyvinyl chloride [PVC] and other resins.
[0153] The implementation methods have been described above. However, it should be understood that various changes can be made to the methods and specific circumstances without departing from the spirit and scope of the claims.
[0154] Example
[0155] The present disclosure will now be described in more detail by way of examples, but the present disclosure is not limited to these examples.
[0156] The various characteristics described in this specification were measured using the following methods.
[0157] (Determination of unstable terminal base)
[0158] The granules were rolled using a hydraulic press to produce a membrane with a thickness of approximately 0.3 mm. The membrane was then analyzed using an FT-IR Spectrometer 1760X (manufactured by Perkin-Elmer).
[0159] Obtain the differential spectrum with the standard sample (the sample has been fully fluorinated until no substantial difference is found in the spectrum), read the absorbance of each peak, and calculate the absorbance relative to 1×10 using the following formula. 6 The number of unstable terminal groups of a carbon atom.
[0160] Compared to 1×10 6 The number of unstable terminal groups equal to the number of carbon atoms = (I×K) / t
[0161] (I: absorbance, K: correction factor, t: film thickness (unit: mm))
[0162] The correction coefficients (K) for each unstable terminal basis are as follows.
[0163] -COF(1884cm -1 )...405
[0164] -COOH(1813cm -1 1775cm -1 )...455
[0165] -COOCH3(1795cm -1 )...355
[0166] -CONH2(3438cm -1 )...480
[0167] -CH2OH(3648cm -1 )...2325
[0168] (Determination of -CF2H terminal group)
[0169] The measurement was performed using an AC300 nuclear magnetic resonance apparatus (manufactured by Bruker-Biospin), with the measurement temperature set to the melting point of fluoropolymer (A) +20°C. 19 F-NMR determination, obtained by integrating the peaks originating from the presence of the -CF2H group with the integrals of other peaks.
[0170] (SSG)
[0171] The determination was performed according to ASTM D4895-89, based on the water displacement method.
[0172] (Melting point)
[0173] Using a DSC (RDC220 manufactured by Seiko Electronics Co., Ltd.), the temperature corresponding to the peak measured at a heating rate of 10°C / min is taken as the melting point.
[0174] (Thermal decomposition temperature)
[0175] The 1% weight reduction temperature was determined by TG when the air was heated at 10°C / min.
[0176] (MFR)
[0177] The values are measured according to ASTM D-1238 using a KAYENESS Melt Indexer Series 4000 (manufactured by Yasuda Seiki Co., Ltd.) with a die head of 2.1 mm in diameter and 8 mm in length, at 372°C and a 5 kg load.
[0178] The examples and comparative examples are implemented using the following methods.
[0179] (Preparation of FEP pellets)
[0180] Fluorinated FEP pellets were prepared using the same method as in Example 1 of Japanese Patent Application Publication No. 2017-128119. The resulting pellets (TFE / HFP / PPVE copolymer) had a TFE / HFP / PPVE ratio of 87.9 / 11.1 / 1.0 (mass ratio), a melting point of 261°C, an MFR of 38 g / 10 min, and a total number of unstable end groups and -CF2H end groups relative to 1 × 10⁻⁶. 6 The number of carbon atoms is 0.
[0181] (Preparation of premixed granules for wire forming (Step 1))
[0182] FEP pellets (MFR: 38 g / 10 min) and additives were compounded using a twin-screw extruder with the barrel and die heads set to the temperatures shown in Table 1 to produce masterbatch pellets. The additive concentration in the masterbatch pellets was 2 to 5 times that in the premixed pellets.
[0183] The obtained masterbatch granules and FEP granules are mixed in a mixer to produce premixed granules with the target additive concentration.
[0184] [Table 1]
[0185] (Evaluation of foamed wire molding (process 2))
[0186] As an extruder for foam molding, an extruder and system manufactured by Hijiri Manufacturing Ltd., a gas injection nozzle manufactured by Micodia, and a crosshead manufactured by Unitech were used. The extruder configuration and conditions are shown in Table 2, and the extruder temperature is shown in Table 3.
[0187] Nitrogen gas is introduced as a foaming agent into the melt mixing section of the extruder for foaming molding, and the premixed granules (composition) prepared above are supplied for extrusion foaming molding. For a core wire with a diameter of 0.30 mm, it is coated with a foamed body with an outer diameter of 0.80 mm and a capacitance of 86 pf / m, thereby obtaining a foamed wire.
[0188] It should be noted that the outer diameter of the wire was measured using a Laser Micro Diamond LDM-303H-XY (manufactured by Takikawa Engineering). The capacitance was measured using a Capacitor AC300 19C (manufactured by Zumbach).
[0189] [Table 2]
[0190] [Table 3]
[0191] (Bubble size)
[0192] SEM images of the cross-section of the foamed wire were taken, and the equivalent diameter of each bubble was calculated through image processing. The average of 100 bubbles was taken as the bubble size.
[0193] (Foaming rate)
[0194] The specific gravity of the fluororesin is calculated as (specific gravity of the fluororesin - specific gravity of the foamed molded body) / specific gravity of the fluororesin) × 100.
[0195] (smoke)
[0196] Visually inspect the upper part of the resin discharge port of the extruder die to confirm whether there are any volatile components.
[0197] (Residue)
[0198] Visually inspect the resin discharge port of the extruder die for any buildup.
[0199] (Surface condition)
[0200] When evaluating the feel of the surface of the foamed wire, the degree of grip (protrusion) is assessed according to the following criteria.
[0201] Excellent: It didn't get caught.
[0202] Good: Few hanging
[0203] Slightly undesirable: There is some hanging.
[0204] Negative: Hanging too much
[0205] (Surface roughness)
[0206] The surface of the foamed wire was measured using a laser microscope (VK-X1000) manufactured by KEYENCE. The obtained image data was then subjected to quadratic surface correction of the specified wire area using surface shape correction. After the correction was performed, the surface roughness of 500×2000μm was calculated.
[0207] (Number of sparks)
[0208] Measurements were taken at 1500V using a Beta LaserMike Sparktester HFS1220. 4 The number of sparks in m.
[0209] (Content of fluorine-based low-molecular-weight compounds)
[0210] The sample was pulverized by cryogenic grinding, and the resulting powder was dispersed in methanol. Extraction was then performed by ultrasonic treatment at 60°C for 2 hours. The extract was quantified using liquid chromatography-mass spectrometry (LC-MS / MS), and the obtained value was taken as the content.
[0211] (Dielectric constant, dielectric loss tangent)
[0212] The target additive concentration of the premixed granules (resin composition before foaming) was determined by the cavity resonator method at a frequency of 6 GHz.
[0213] (The state of the tetrapyrrole cyclic compound (B) at the molding temperature)
[0214] Using a polarizing microscope equipped with a heated stage, observe whether the tetrapyrrole cyclic compound (B) exists in a solid state when heated to a specified temperature.
[0215] Example 1
[0216] In step 1, granules containing 1 part by mass of copper phthalocyanine (manufactured by Tokyo Chemical Industry Co., Ltd., melting point: no peak detected below 350°C, thermal decomposition temperature: 388°C) are produced relative to 100 parts by mass of FEP granules. In step 2, foamed wire is formed at an extrusion speed (screw speed) of 15 rpm, a nitrogen flow rate of 16 cc / min, and a traction speed of 100 m / min to obtain a foamed wire with an outer diameter of 0.80 mm and a capacitance of 86 pF / m.
[0217] No smoke or residue was observed during molding, and the spark count was 5 / 10. 4 The foaming rate of the obtained foamed wire is 43%, the bubble size is 21 μm, which is good. The surface texture is also extremely good, and the surface roughness is 6.8 μm, which is very good.
[0218] In addition, copper phthalocyanine does not decompose, dissolve in FEP, or melt at the molding temperature during foaming.
[0219] Furthermore, no low-molecular-weight fluorine compounds were detected in the granules used or in the coating of the foamed wires. No low-molecular-weight fluorine compounds were also detected in the comparative examples described later.
[0220] Furthermore, the formation of independent bubbles was confirmed by the SEM images used to calculate the bubble size. Independent bubbles were also formed in subsequent comparative examples 1, 3, and 4.
[0221] Comparative Example 1
[0222] Boron nitride (MGP manufactured by Denka Corporation) was used as an additive, and the foamed wire was otherwise manufactured using the same method as in Example 1.
[0223] No smoke or residue was observed during the molding process, but the surface condition of the wires was poor, with more than 300 sparks per 10 wires. 4 The surface roughness of the foamed wire was very poor, with a bubble size of up to 36 μm and a surface roughness of 12.4 μm.
[0224] Comparative Example 2
[0225] Irgaclear XT386 (a transparent nucleating agent for polypropylene manufactured by BASF) was used as an additive. In addition, foamed wires were attempted to be made using the same method as in Example 1, but frequent smoke and residue occurred, and the desired foamed wire could not be obtained.
[0226] Comparative Example 3
[0227] As an additive, 0.5 parts by weight of potassium titanate (TISMO D manufactured by Otsuka Chemical Co., Ltd.) was used, and the foamed wire was otherwise made by the same method as in Example 1.
[0228] No smoke or residue was observed during the molding process, but the surface condition of the wires was slightly poor, with a spark count exceeding 100 / 10. 4 The surface roughness of the foamed wire was 10.1 μm, which is very poor. The analysis results showed that the bubble size was 27 μm, which is good, but the surface roughness was 10.1 μm, which is poor.
[0229] Comparative Example 4
[0230] No additives are used; the foamed wires are made using the same method as in Example 1.
[0231] No smoke or residue was observed during molding, and the spark count was 0 / 10. 4m, good, but the analysis results of the obtained foamed wire showed that the bubble size was 103μm, which is very large.
[0232] Comparative Example 5
[0233] As additives, 0.01 parts by weight of sodium fluorobutane sulfonate (fluorinated surfactant) and 0.4 parts by weight of boron nitride were used, otherwise the foamed wire was made by the same method as in Example 1.
[0234] No smoke or residue was observed during the molding process, but the surface condition of the wires was poor, with more than 100 sparks per 100 wires. 4 The analysis results of the obtained foamed wire show that the bubble size is 30 μm, which is good, but the surface roughness is 12.3 μm, which is very poor.
[0235] [Table 4]
Claims
1. A resin composition for foaming molding, comprising a fluoropolymer (A) and a tetrapyrrole cyclic compound (B).
2. The resin composition for foaming molding as described in claim 1, wherein, The fluororesin (A) is a fluororesin that can be melt-formed.
3. The resin composition for foaming molding as described in claim 1 or 2, wherein, The fluororesin (A) is selected from at least one of the groups consisting of tetrafluoroethylene / hexafluoropropylene copolymers and tetrafluoroethylene / perfluoro(alkyl vinyl ether) copolymers.
4. The resin composition for foaming molding according to any one of claims 1 to 3, wherein, The fluororesin (A) is a tetrafluoroethylene / hexafluoropropylene copolymer.
5. The resin composition for foaming molding according to any one of claims 1 to 4, wherein, The fluoropolymer (A) has undergone fluorination treatment.
6. The resin composition for foaming molding according to any one of claims 1 to 5, wherein, The content of the fluoropolymer (A) is 80% to 99.99% by mass.
7. The resin composition for foaming molding according to any one of claims 1 to 6, wherein, The content of the fluoropolymer (A) is 97% by mass or more and less than 99.85% by mass.
8. The resin composition for foaming molding according to any one of claims 1 to 7 is substantially free of fluorine-based low molecular weight compounds.
9. The resin composition for foaming molding according to any one of claims 1 to 8, wherein, The tetrapyrrole cyclic compound (B) has a phthalocyanine skeleton.
10. The resin composition for foaming molding according to any one of claims 1 to 9, wherein, The tetrapyrrole cyclic compound (B) is a metal phthalocyanine.
11. The resin composition for foaming molding according to any one of claims 1 to 10, wherein, The tetrapyrrole cyclic compound (B) is copper phthalocyanine.
12. The resin composition for foaming molding according to any one of claims 1 to 11, wherein, The content of the tetrapyrrole cyclic compound (B) is 0.1 to 20 parts by mass relative to 100 parts by mass of the fluororesin (A).
13. The resin composition for foaming molding according to any one of claims 1 to 12, wherein, The content of the tetrapyrrole cyclic compound (B) is 0.5 to 2.0 parts by mass relative to 100 parts by mass of the fluoropolymer (A).
14. A foamed molded article formed using the foamed molding resin composition according to any one of claims 1 to 13.
15. A method for manufacturing a foamed molded article, comprising a step of foaming a resin composition for foaming molding according to any one of claims 1 to 13.
16. A foamed wire having a conductor and a foamed insulation layer formed on the conductor using any one of claims 1 to 13 of the resin composition for foaming.
17. A method for manufacturing a foamed wire, comprising the step of forming a foamed insulating layer on a conductor using a foaming molding resin composition according to any one of claims 1 to 13.
Citation Information
Patent Citations
Expandable fluoropolymer composition
JP1998045931A
Expandable resin composition, and foam and coaxial insulation cable using the composition
JP2005206745A
Pellet of fluorine resin, electric wire and method for producing the same
JP2017128119A
Foam molding composition, foamed molded body, electric wire, method for manufacturing foamed molded body, and method for manufacturing electric wire
JP2022028640A
Foam nucleation system for fluoropolymers
US4764538A